Heterotopic Ossification: Clinical Features, Basic Researches, and Mechanical Stimulations - Xu, Yili; Huang, Mei; He, Wenzhen; He, Chen; Chen, Kaixuan; Hou, Jing; Huang, Min; Jiao, Yurui; Liu, Ran; Zou, Nanyu; Liu, Ling; Li, Changjun (Frontiers in Cell and Developmental Biology, 2022)
Heterotopic ossification (HO) is defined as the occurrence of extraskeletal bone in soft tissue. Although this pathological osteogenesis process involves the participation of osteoblasts and osteoclasts during the formation of bone structures, it differs from normal physiological osteogenesis in many features. In this article, the primary characteristics of heterotopic ossification are reviewed from both clinical and basic research perspectives, with a special highlight on the influence of mechanics on heterotopic ossification, which serves an important role in the prophylaxis and treatment of HO.